2021
DOI: 10.1016/j.wroa.2020.100086
|View full text |Cite
|
Sign up to set email alerts
|

Early-pandemic wastewater surveillance of SARS-CoV-2 in Southern Nevada: Methodology, occurrence, and incidence/prevalence considerations

Abstract: The World Health Organization (WHO) classified COVID-19 as a global pandemic, with the situation ultimately requiring unprecedented measures to mitigate the effects on public health and the global economy. Although SARS-CoV-2 (the virus responsible for COVID-19) is primarily respiratory in nature, multiple studies confirmed its genetic material could be detected in the feces of infected individuals, thereby highlighting sewage as a potential indicator of community incidence or prevalence. Numerous wastewater s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
170
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 197 publications
(195 citation statements)
references
References 49 publications
16
170
3
Order By: Relevance
“…showing N1 to be more sensitive than N2 with up to 0.3 log difference. Also, contradictory results were observed by Gerrity et al (2021) studying two WWTPs. N1 was more frequently recorded for one WWTP, whereas it was N2 for the second WWTP.…”
Section: N1 and N2 Targets Responsementioning
confidence: 95%
“…showing N1 to be more sensitive than N2 with up to 0.3 log difference. Also, contradictory results were observed by Gerrity et al (2021) studying two WWTPs. N1 was more frequently recorded for one WWTP, whereas it was N2 for the second WWTP.…”
Section: N1 and N2 Targets Responsementioning
confidence: 95%
“…Comparability of data obtained from grab samples with 24-h composite samples obtained by autosampler has been investigated as part of several SARS-CoV-2 wastewater surveillance programs (Curtis et al, 2020;Bivens et al, 2021b;Gerrity et al, 2021). While general agreement between the approaches has been reported, groups report within-day variability in terms of detection of SARS-CoV-2 using the grab sample approach, a concern that is magnified when dealing with a congregate living facility housing a small population such as a university residence hall.…”
Section: Campus Wastewater Surveillance For Sars-cov-2mentioning
confidence: 99%
“…One such method is wastewater-based epidemiology (WBE), which has provided community-scale information on drug use, personal care products, antibiotic resistance, and pathogen circulation (Choi et al, 2018). SARS-CoV-2 is a promising candidate for WBE because its RNA is detected in stool of infected individuals (Li et al, 2021;Parasa et al, 2020), and wastewater surveillance has been shown to provide early detection of population-level increases in occurrence compared to clinical data in some locations (Ahmed et al, 2021;D'Aoust et al, 2021a;Gerrity et al, 2021;Hata and Honda, 2020;Medema et al, 2020;Nemudryi et al, 2020;Peccia et al, 2020;Randazzo et al, 2020bRandazzo et al, , 2020a.…”
Section: Introductionmentioning
confidence: 99%